ANALISIS PENGARUH PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP KINERJA KEUANGAN (Studi Pada Perusahaan Yang Terdaftar di Bursa Efek Jakarta) - Widaryanti . (STIE Pelita Nusantara Semarang, 2007)
Orientation displacement in business causes more width space of company social responsibility. Company isn't only give responsibility to creditor, investor and government, but also to others like public community and employee.This study had goals to analyze the effect of responsibility report in company financial statement with financial performance of go public companies in Jakarta Stock Exchange. Social responsibility report had four themes. There is energy and environment, employee, product and costumer, and social theme. Financial performance proxies on Return on Assets (ROA).Sample in this research is curtained with purposive sampling method and obtained 40 go public company has convey statement report 2004 in Jakarta Stock Exchange. This analysis uses multiple regressions. The result show that energy and environment, employee, product and costumer, and social theme with simultan regression not effect with financial performance. Partial regression show that only energy and environment theme have effect positive significant with financial performance. Employee, product and costumer, and social theme not effect with financial performance. This study also shows that determination coefficient is 19.2 %; means that a lot ofother .variables out of this study can affect company financial performance.